The Essential of the 1945 Constitution and the Agreement of the Amendment of the 1945 Constitution: A Comparison of the Constitutional Amendment - Aidul Fitriciada Azhari (Fakultas Hukum Universitas Islam Indonesia, 2011)
This research discusses two issues which are: First, (1) comparison of similarities and differences of the essence of Constitution and the amendment agreement of Constitution; Second, (2) consequence of those differences towards the current development of Constitution. Normative legal research and post-colonial theory methods are used to analyze the issues. Data are collected from legal materials through literary study and documentary study. With those methods, this research found that the difference between 1950 and 1999 agreement shows inconsistency and divergence in viewing Constitution. Besides that, the agreement on essence of Constitution is performed based on decolonialization paradigm, while the consent of People’s Consultative Assembly in 1999 was mostly based on democractization paradigm.